2017
DOI: 10.1007/s41825-017-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy policy trends and recommendations for GCC countries

Abstract: Policies to support the deployment of renewable energy technologies have been widely established for power generation, heating, cooling, and transportation. However, as renewable energy technologies have become increasingly cost-competitive and more widely deployed, policymakers have begun to focus their attention on the adaption of existing policies to reflect the rapidly changing economics of these technologies and the impacts they have may have on the energy systems in which they are deployed. Optimal renew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Using a different approach, a renewable energy policy trend analysis was made for the GCC countries [7]. The study indicated that Qatar uses natural gas to cover over 60% of their primary energy needs and nearly 100% of their power demand.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different approach, a renewable energy policy trend analysis was made for the GCC countries [7]. The study indicated that Qatar uses natural gas to cover over 60% of their primary energy needs and nearly 100% of their power demand.…”
Section: Previous Studiesmentioning
confidence: 99%
“…As a conclusion, the paper indicated that the tendency in renewable energy policy design is the support the integration of cost-effective renewables into energy systems with a low impact on government finances. This trend is significant in the power sector where environmentally friendly energy technologies are becoming economically viable across the world at an accelerated pace [7]. An analysis of the policy variation in the GCC counties focusing on the adaption of renewable energy technologies was also performed [8].…”
Section: Previous Studiesmentioning
confidence: 99%
“…(1) r is the rating on a Likert scale (1-5) as for the impact on construction efficiency for a specific element influencing construction profitability, nr is the number of respondents providing a specific Likert scale rating r, N is the aggregate number of respondents to a specific question [6][4], [16], [17]. The value given to the Likert scale rating is as follows:…”
Section: Relative Importance Indexmentioning
confidence: 99%
“…The criterial of smart practice and negative side-effects of projects in bioenergy, biomass and biogas production have been recently explored by Ciervo andSchmitz (2017 or Martinát et al (2017). Abdmouleh et al (2015), Kitzing et al (2012) and Griffiths (2017) studied best practices concerning national renewable energy policies in general. Thapar et al (2016), on the other hand, focused more on the perspective of developing countries, identifying innovative practices followed in India which have enabled accelerated renewable energy capacity with minimal financial obligations.…”
Section: Theoretical Departures: From ´Best Practice´ To ´Smart Practmentioning
confidence: 99%